18.1k views
0 votes
Find f. f ''(x) = 4 + 6x + 36x2, f(0) = 2, f (1) = 10

User Duy Nguyen
by
5.9k points

1 Answer

3 votes
It has been a while since I have done differnetial equations but I think here you only need to integrate twice.
4 + 6x + 36x^2= 2*(2+3x+18x^2)

Integrate 2+3x+18x^2 to get 2x+3/2x^2+18/3x^3 +C = 2x +3/2x^2+6x^3 + C
Integrate again now this: 2x +3/2x^2+6x^3 + C to get x^2 + 1/2x^3+3/2x^4 +Cx +D
Now multiply by two (as I have taken out 2 earlier)
2x^2+x^3+3x^4+2Cx+D

Now use the initial conditions.
f(0)=2
D=2
f(1)=10
2+1+3+2C+2=10
C=1

So the solution is: (ordered by power, as neat mathematicans would do)
f(x)= 3x^4 + x^3 + 2x^2 + 2x +2

User Reese Moore
by
6.4k points